Stereotypes, Students’ Perceptions and Inherent Creativity: Further Australian Evidence - Peter Baxter; Marie Kavanagh (Australasian Accounting, Business and Finance Journal, 2013)
The objectives of this study are to: ascertain how first year university students perceive accounting in a time period following the high profile corporate collapses of the early 21st century; understand the factors that influence these perceptions; and determine if there is an association between students’ perceptions of accounting and their inherent creativity. The findings of the study show that the majority of first year university students still hold a traditional stereotypical perception of accounting. School teachers and subjects were reported by the students as being the main influences on their perceptions. Students’ perceptions of accounting are also linked to their inherent creativity. A limitation of the study is that the sample is drawn from students at two Australian universities. Therefore, the results may not generalise to other institutions. This study contributes to the existing body of knowledge on students’ perceptions of accounting and the impact of various factors. There are implications for educators in designing appropriate curricula and the promotion of accounting by the accounting profession.
Keywords: Perceptions; Personality; Accounting; Students